Telegram from Assemblyman Art Torres to Jane Tolmach - Art Torres:::::: (1976)
This June 8, 1976 telegram from Assemblyman Art Torres congratulates Jane Tolmach on her "tremendous victory." He expressed his anticipation of working with her toward an even greater victory in the November general election.